The slash-and-burn agriculture: a system in transformation - Nelson Novaes Pedroso Júnior (Boletim do Museu Paraense Emílio Goeldi. Ciências Humanas, 2008)
Slash-and-burn agriculture has been practiced for thousands of years in the forests around the world, especially in the tropics, where it provides for the livelihood of countless poor rural populations. Characterized by an array of techniques based on crop diversification and shifting land use, this cultivation system has on the utilization of forest decomposing vegetation´s energetic capital its main asset. Many studies claim that slash-and-burn agriculture is sustainable only when performed under conditions of low human demographic density and maintenance or even increase of local biodiversity. However, it is growing in the academic literature, as well as in development debates, the concern regarding the role that this system has been playing in the deforestation of the planet´s tropical forests. This process appears to be closely linked to changes in land use patterns (agricultural intensification) and urban and rural demographic growth. On the thread of these concerns, this article presents a critical review of the international and national academic literature on slash-and-burn agriculture. Thus, this review intend to draw a broad scenario of the current academic debate on this issue, as well as to identify the main alternatives strategies proposed to maintain or replace this cultivation system.